"Your Mysterious Instruments": American Devices and Imperial Designs in Cold War Archaeology. (19th May 2022) - Meskell, Lynn; LaPorte, Sarah
ABSTRACT: This paper tracks a world of instruments and global designs in a new era of archaeology, spearheaded by Froelich Rainey in his role as Director of the University of Pennsylvania Museum of Archaeology and Anthropology. Post-WWII scientific development, industrial-military-academic partnerships, and American adventurism were all brought together through Rainey's archaeological expeditions. During the 1960s, Penn's field projects were strategically positioned across the globe, with many trialing a novel technique or different device: Rainey launched a prototype submarine off the Turkish coast, magnetometers and sonic devices across Italy, resistivity in Mexico, and infrared aerial cameras over the Mediterranean. Archaeological innovation was tied to, and developed directly out of, US nuclear ambition and the leveraging of 'peaceful' atomic research, and American Cold War collaborations that united science, exploration, and culture for mutual benefit. Here we underscore the connectivities between diverse actors and activities, nuclear science, tech companies, private foundations, and philanthropists, coupled with the military and intelligence community.